(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The e-commerce represents a commercial activity of considerable upsurge. Nevertheless, there are certain factors that prevent its take-off and effective consolidation. One of them is, justly, the potential lack of consumer confidence. However, certain instruments have been recently created -like codes of conduct-, in order tomitigate and, if it is possible, eradicate the factors that cause distrust through a relatively significant improvement of the applicable legislation. The code of conduct Euro-Label stands out from the variety of codes of conduct that are currently used ine-commerce.